Evaluasi Pelaksanaan PILKADA Serentak Tahun 2020 di Kabupaten Yalimo - Yabansabra, Rudolf; Torobi, Renida J. (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2024)
This article analyzes the assessment of the implementation of the 2020 Yalimo Regency elections using three indicators: effectiveness, efficiency, and responsiveness. The research uses a qualitative approach through a literature study, drawing data from various sources such as journal articles, government reports, and news. The data analysis includes categorization, presentation, and making conclusions. The results show that the implementation of the regional elections in Yalimo Regency is not optimal. In terms of effectiveness, disputes, riots, and re-voting problems were identified. The organization of the elections is considered highly inefficient due to budget irrationality and increased costs after the discourse of re-voting and riots. The responsiveness aspect shows both positive and negative responses to decisions made during the elections.